Class I and II NADPH-cytochrome P450 reductases exhibit different roles in triterpenoid biosynthesis in Lotus japonicus - Istiandari, Pramesti; Yasumoto, Shuhei; Seki, Hikaru; Fukushima, Ery Odette; Muranaka, Toshiya (Frontiers in Plant Science, 2023)
Lotus japonicus produces triterpenoids, including betulinic acid, oleanolic acid and soyasaponins. Cytochrome P450 monooxygenases (CYPs) are enzymes that play critical roles in the structural diversification of triterpenoids by catalyzing site-specific oxidations of the triterpene scaffold. To perform site-specific oxidations, CYPs require electrons transferred by NADPH-cytochrome P450 reductase (CPR), which is classified into two main classes, class I and class II, based on their structural difference. L. japonicus has one CPR class I gene (LjCPR1) and a minimum of two CPR class II genes (LjCPR2-1 and LjCPR2-2). CPR classes I and II from different plants have been reported to be involved in different metabolic pathways. This study revealed that LjCPR1, CYP716A51, and LUS were down-regulated by methyl jasmonate (MeJA) treatment which resulted in no change in betulinic acid and lupeol content. In contrast, LjCPR2s, bAS, CYP93E1, and CYP72A61 were significantly upregulated by MeJA treatment, followed by a significant increase of the precursors for soyasaponins, i.e. β-amyrin, 24-OH β-amyrin, and sophoradiol content. Triterpenoids profile analysis of LORE1 insertion and hairy root mutants showed that the loss of the LjCPR2-1 gene significantly reduced soyasaponins precursors but not in Ljcpr1 mutants. However, Ljcpr1 and Ljcpr2-1 mutants showed a significant reduction in lupeol and oleanolic, ursolic, and betulinic acid contents. Furthermore, LjCPR1, but not LjCPR2, was crucial for seed development, supporting the previous notion that CPR class I might support plant basal